Bigfoot - Karst, Ken (Mankato, MN : Creative Education, 2015)
"An investigative approach to the curious phenomena and mysterious circumstances surrounding the creature known as Bigfoot, from reported sightings to hoaxes to hard facts"--
Bigfoot country -- The bigfoot map -- Seeing and not believing -- Bigfoot: an open or closed case? -- Invite a bigfoot for dinner! -- The father of cryptozoology -- Bigfoot: this exit -- Don't shoot! -- Field notes.
Includes bibliographical references (page 47) and index.
Keywords: Sasquatch -- Juvenile literature